2015
DOI: 10.5041/rmmj.10209
|View full text |Cite
|
Sign up to set email alerts
|

Role of Regulatory T Cells (Treg) and the Treg Effector Molecule Fibrinogen-like Protein 2 in Alloimmunity and Autoimmunity

Abstract: CD4+CD25+Foxp3+ regulatory T cells (Treg) are critical to the maintenance of immune tolerance. Treg are known to utilize a number of molecular pathways to control immune responses and maintain immune homeostasis. Fibrinogen-like protein 2 (FGL2) has been identified by a number of investigators as an important immunosuppressive effector of Treg, which exerts its immunoregulatory activity by binding to inhibitory FcγRIIB receptors expressed on antigen-presenting cells including dendritic cells, endothelial cells… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 96 publications
(122 reference statements)
0
15
0
Order By: Relevance
“…Thus, understanding how LGT-resident eTregs suppress self-reactive T cell clones in the target tissue will be an important question to address. The transcriptional signatures derived in this study point to new molecular candidates: Areg, a ligand for EGFR that stimulates Treg-suppressive functions (39) and was recently demonstrated to have a key role in Treg-mediated tissue repair (40); Fgl2, a secreted factor with potent immunoregulatory properties (41); or Itgb8, which is required for the activation of latent TGF-b in Tregs (42).…”
Section: Discussionmentioning
confidence: 94%
“…Thus, understanding how LGT-resident eTregs suppress self-reactive T cell clones in the target tissue will be an important question to address. The transcriptional signatures derived in this study point to new molecular candidates: Areg, a ligand for EGFR that stimulates Treg-suppressive functions (39) and was recently demonstrated to have a key role in Treg-mediated tissue repair (40); Fgl2, a secreted factor with potent immunoregulatory properties (41); or Itgb8, which is required for the activation of latent TGF-b in Tregs (42).…”
Section: Discussionmentioning
confidence: 94%
“…Individuals using long-term immunosuppressive medications (azathioprine, cyclophosphamide, and cyclosporine) or those with underlying immunologic abnormalities, such as an autoimmune disease or viral infection, are particularly at risk of malignancy [25]. Immune dysregulation plays a vital role in both initiation and progression of autoimmune disease [26]. The evidence indicates that immune suppression contributes to cancer progression.…”
Section: Discussionmentioning
confidence: 99%
“…overexpressed in patients with IBD (1). Additionally, fibrinogen-like protein 2 (FGL2) is one of the immunosuppressive cytokines expressed by Treg cells and has been identified to be an important effector molecule by which Treg cells exerts their immunosuppressive effects (17)(18)(19)(20). FGL2 has been demonstrated to inhibit the proliferation of T cells and the maturation of bone marrow-derived cells.…”
Section: Elevated Fibrinogen-like Protein 2 In Tnbs-induced Colitis Mmentioning
confidence: 99%
“…FGL2 has been demonstrated to inhibit the proliferation of T cells and the maturation of bone marrow-derived cells. Previous studies have demonstrated that subsets of Treg cells with increased levels of FGL2 are more suppressive and that Treg cells from FGL2 -/mice have been observed exhibit decreased suppressive activity (17,20,21). It was previously identified that the expression of FGL2 in intestinal mucosal biopsies and periphe ral blood was increased in patients with active disease, and decreased in inactive disease.…”
Section: Elevated Fibrinogen-like Protein 2 In Tnbs-induced Colitis Mmentioning
confidence: 99%